(untitled) (Journal of Hama University, 2023)
T The aim of the research is to identify the degree of fourth-grade teachers’ practice of problem-solving skill in the subject of social studies. It also aims to test the significance of the differences between the teachers’ average scores on the problem-solving skill questionnaire due to the variable of years of experience and the variable of academic qualification. To achieve these goals, the descriptive analytical approach was used. Through the application of a questionnaire consisting of (30) items, the research was applied in the first semester of the academic year 2022/2023 on a random sample consisting of (180) male and female teachers from the fourth grade teachers of the first cycle schools in the city of Hama. The research reached the following results: - The degree of fourth-grade teachers’ practice of problem-solving skill in social studies subject was medium. - There are statistically significant differences about the degree of fourth-grade teachers’ practice of the problem-solving skill in the subject of social studies, due to the variable number of years of experience, about (5-10) years. - there were no statistically significant differences about the degree of fourth-grade teachers’ practice of problem-solving skill in social studies subject due to the educational qualification variable (secondary school or institute/university). In light of the results, the research presented a set of recommendations, including holding training courses for teachers before and during service, in order to train them on methods of developing the problem-solving skill of basic stage students in general and the fourth grade in particular.